Artificial graphite negative electrode active material and method for evaluating high-temperature cycle life thereof

CN122868524APending Publication Date: 2026-10-02WANHUA CHEM GRP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510392509.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-02

AI Technical Summary

Technical Problem

倘若包覆均一性低、包覆层厚度参差不齐、材料表面暴露过多缺陷,包覆和未包覆的界面容易发生“边缘效应”,在大倍率充放电的过程中,负极表面容易出现析锂的现象,这不仅会对电芯安全产生较大影响,同时会导致高温循环容量保持率大幅下降

Benefits of technology

[0012]本申请实施例的人造石墨负极活性材料带来的优点和技术效果,本申请实施例通过对人造石墨负极活性材料的振实密度、极片取向指数、50%体积分布粒径、90%体积分布粒径、无序度和比表面积之间的关系进行控制,使人造石墨负极活性材料具有优异的高温循环性能,同时也赋予了人造石墨负极活性材料良好的倍率性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005338726870000121
    Figure BDA0005338726870000121
  • Figure BDA0005338726870000131
    Figure BDA0005338726870000131
Patent Text Reader

Abstract

The application discloses artificial graphite negative active material, which satisfies: HL=TD*(OI+Dv50+Dv90) / (100*R*S), HL>2.0; wherein, TD is the tap density of the artificial graphite negative active material, unit is g / cm 3 ; OI is the orientation index of the artificial graphite negative active material; Dv50 is the 50% volume distribution particle size of the artificial graphite negative active material, unit is μm; Dv90 is the 90% volume distribution particle size of the artificial graphite negative active material, unit is μm; R is the disorder degree of the artificial graphite negative active material, ID / IG value of Raman test; S is the specific surface area of the artificial graphite negative active material, unit is m 2 / g. The artificial graphite negative active material has not only excellent high-temperature cycle performance, but also good rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of secondary battery technology, specifically relating to an artificial graphite negative electrode active material and its preparation method. Furthermore, this application also relates to a secondary battery and an electrical device. Even further, this application also relates to a method for evaluating the high-temperature cycle life of an artificial graphite negative electrode active material. Background Technology

[0002] In recent years, the lithium-ion battery industry has experienced rapid growth, with electric vehicle penetration exceeding 50%. As products are upgraded and iterated, consumers' requirements for lithium-ion batteries are no longer limited to super-fast charging performance. They also have increasingly higher requirements for high-temperature long-cycle performance, reliability, and safety.

[0003] Currently, the preparation of commercially available rate-capable anode materials mainly uses natural graphite and artificial graphite as substrates, coated with an amorphous carbon layer. For graphite anode materials modified by coating, the characteristics of the amorphous carbon layer play a crucial role in the rate performance of the anode material. For example, the higher the coating uniformity, the more uniform the coating thickness, and the fewer surface defects, the fewer side reactions occur during the charge and discharge process of lithium-ion batteries, resulting in better high-rate charge and discharge performance and high-temperature long-cycle performance. If the coating uniformity is low, the coating thickness is uneven, and too many defects are exposed on the material surface, the interface between the coated and uncoated layers is prone to "edge effects." During high-rate charge and discharge, lithium plating is likely to occur on the anode surface, which not only significantly affects cell safety but also leads to a substantial decrease in high-temperature cycle capacity retention. In the material development process, researchers often spend a lot of time acquiring cycling data, resulting in excessively long material design and development cycles as well as downstream battery design and development cycles, and reduced production efficiency. Therefore, how to quickly construct materials that balance high-temperature cycling performance and fast charging capability has become a pressing challenge in the field of anode material development. Summary of the Invention

[0004] This application aims to at least partially solve one of the technical problems in the related art. To this end, embodiments of this application propose an artificial graphite anode active material and its preparation method. By ensuring that parameters such as the 50% volume distribution particle size Dv50, 90% volume distribution particle size Dv90, tap density TD, electrode orientation index OI, disorder degree R, and specific surface area S of the artificial graphite anode active material meet the requirements of the relevant formula, the high-temperature cycling performance of the artificial graphite anode active material is effectively improved, while also taking into account its rate performance.

[0005] Embodiments of the present application provide an artificial graphite negative electrode active material, which satisfies: HL=TD*(OI+Dv50+Dv90) / (100*R*S), HL>2.0;

[0006] wherein, TD is the tap density of the artificial graphite negative electrode active material, with a unit of g / cm 3 ;

[0007] OI is the orientation index of an electrode plate prepared from the artificial graphite negative electrode active material;

[0008] Dv50 is the 50% volume distribution particle size of the artificial graphite negative electrode active material, with a unit of μm;

[0009] Dv90 is the 90% volume distribution particle size of the artificial graphite negative electrode active material, with a unit of μm;

[0010] R is the disorder degree of the artificial graphite negative electrode active material, which is the ID / IG value measured by Raman test;

[0011] S is the specific surface area of the artificial graphite negative electrode active material, with a unit of m 2 / g.

[0012] With respect to the advantages and technical effects brought by the artificial graphite negative electrode active material of the embodiments of the present application, the embodiments of the present application control the relationship among the tap density, electrode plate orientation index, 50% volume distribution particle size, 90% volume distribution particle size, disorder degree and specific surface area of the artificial graphite negative electrode active material, so that the artificial graphite negative electrode active material has excellent high-temperature cycle performance, and also endows the artificial graphite negative electrode active material with good rate performance.

[0013] In some embodiments, 2.0 < HL < 16.0, preferably 2.0 < HL < 9.0.

[0014] In some embodiments, the tap density TD is 0.8-1.5 g / cm 3 , preferably 1.0-1.3 g / cm 3 .

[0015] In some embodiments, the electrode plate orientation index OI is 4-20, preferably 10-15.

[0016] In some embodiments, the 50% volume distribution particle size Dv50 is 6-20 μm, preferably 10-15 μm.

[0017] In some embodiments, the 90% volume distribution particle size Dv90 is 15-40 μm, preferably 20-25 μm.

[0018] In some embodiments, the disorder degree R is 0.04-0.5, preferably 0.05-0.2.

[0019] In some embodiments, the specific surface area S is 0.6-2.0 m². 2 / g, preferably 0.6-1.5m 2 / g.

[0020] This application also provides a method for preparing an artificial graphite anode active material, comprising the following steps:

[0021] a. After pretreatment, the raw materials are ground, granulated and / or shaped, and then pre-carbonized.

[0022] b. Graphitize the material obtained after pre-carbonization in step a;

[0023] c. Demagnetize the material after graphitization treatment in step b to obtain artificial graphite anode active material.

[0024] The advantages and technical effects of the preparation method of the artificial graphite anode active material in this application are as follows: By using the method of this application to prepare the artificial graphite anode active material, the parameters such as the 50% volume distribution particle size Dv50, the 90% volume distribution particle size Dv90, the tap density TD, the electrode orientation index OI, the disorder degree R, and the specific surface area S of the prepared artificial graphite anode active material meet the requirements of the relationship HL=TD*(OI+Dv50+Dv90) / (100*R*S) and HL>2.0, which effectively improves the high-temperature cycling performance of the artificial graphite anode active material, while also taking into account the rate performance of the artificial graphite anode active material.

[0025] In some embodiments, in step a, the raw material includes at least one of needle coke, petroleum coke, pitch coke, and isotropic coke; the pretreatment includes crushing and / or drying; the temperature of the precarbonization treatment is 500-1000℃, and the time of the precarbonization treatment is 1-5h.

[0026] In some embodiments, in step b, the equipment used for graphitization includes at least one of the following: an Atchison crucible furnace, an Atchison box furnace, a horizontal continuous graphitization furnace, a vertical continuous graphitization furnace, a medium-frequency furnace, a medium-frequency continuous furnace, and an electric arc smelting furnace; the temperature of the graphitization is 2000-3000℃, and the time of the graphitization is 1-5h.

[0027] This application also provides a secondary battery, including the artificial graphite anode active material of this application embodiment or the artificial graphite anode active material prepared by the method of this application embodiment. The secondary battery of this application embodiment possesses all the advantages brought by the artificial graphite anode active material of this application embodiment, which will not be repeated here.

[0028] This application also provides an electrical device, including a secondary battery as described in this application embodiment. The electrical device of this application embodiment possesses all the advantages of the secondary battery of this application embodiment, which will not be elaborated further here.

[0029] This application also provides a method for evaluating the high-temperature cycle life of artificial graphite anode active materials, including the following steps:

[0030] (1) The 50% volume distribution particle size Dv50, 90% volume distribution particle size Dv90, tap density TD, electrode orientation index OI, disorder degree R, and specific surface area S of the artificial graphite anode active material were determined. The units for Dv50 and Dv90 are μm, and the unit for TD is g / cm³. 3 The unit of S is m. 2 / g;

[0031] (2) Setting the high-temperature cycling performance index of artificial graphite anode active material

[0032] HL=TD*(OI+Dv50+Dv90) / (100*R*S);

[0033] (3). Based on the Dv50, Dv90, TD, OI, R and S measured in step (1), calculate the high temperature cycle performance index HL of the artificial graphite anode active material. When HL > 2.0, the high temperature cycle life of the artificial graphite anode active material is qualified.

[0034] Advantages and technical effects brought by the method for evaluating the high-temperature cycle life of artificial graphite anode active materials according to embodiments of the present application are as follows: 1. In the evaluation method of the embodiments of the present application, by studying the influence of core parameters including 50% volume distribution particle size Dv50, 90% volume distribution particle size Dv90, tap density TD, pole sheet orientation index OI, disorder degree R, and specific surface area S of the artificial graphite anode active material on the high-temperature cycle performance of the graphite anode active material, the relationship between these core parameters and the high-temperature cycle performance of the artificial graphite anode active material is discovered, and a high-temperature cycle performance index HL for artificial graphite anode active materials is proposed as HL=TD*(OI+Dv50+Dv90) / (100*R*S). By judging the magnitude of the HL value, the high-temperature cycle life of the artificial graphite anode active material can be effectively evaluated; 2. The evaluation method in the embodiments of the present application can quickly predict the quality of the high-temperature cycle performance of the artificial graphite anode active material before assembling into a test battery. The evaluation method is simple in operation and accurate in judgment result, and it is not necessary to assemble into a test battery to test its high-temperature cycle performance, which helps save time, improve efficiency, and facilitate the rapid advancement of model selection in battery research and development and production.

[0035] In some embodiments, 2.0<HL<16.0, preferably 2.0<HL<9.0. Detailed Description

[0036] Embodiments of the present application are described in detail below. The described embodiments are exemplary and are intended to explain the present application, and cannot be construed as a limitation on the present application.

[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present application belongs. The terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present application. The terms "comprise" and "have" and any variations thereof in the description and claims of the present application are intended to cover non-exclusive inclusion.

[0038] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be construed as indicating or implying relative importance or implicitly indicating the number of the indicated technical features, a specific order or a primary-secondary relationship. In the description of the embodiments of the present application, "a plurality" means two or more, unless otherwise specifically defined.

[0039] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0040] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0041] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.

[0042] In the description of the embodiments of this application, the term "multiple" refers to two or more (including two), similarly, "multiple sets" refers to two or more (including two sets), and "multiple pieces" refers to two or more (including two pieces).

[0043] In the present application, the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" mean that the specific feature, structure, material or characteristic described in connection with the embodiment or example is included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the described specific features, structures, materials or characteristics may be combined in a suitable manner in any one or more embodiments or examples. In addition, those skilled in the art can combine and assemble the different embodiments or examples and the features of different embodiments or examples described in this specification without conflicting with each other.

[0044] An embodiment of the present application provides an artificial graphite negative electrode active material, which satisfies: HL=TD*(OI+Dv50+Dv90) / (100*R*S), and HL>2.0;

[0045] wherein, TD is the tap density of the artificial graphite negative electrode active material, with a unit of g / cm 3 ;

[0046] OI is the orientation index of an electrode plate prepared from the artificial graphite negative electrode active material;

[0047] Dv50 is the 50% volume distribution particle size of the artificial graphite negative electrode active material, with a unit of μm;

[0048] Dv90 is the 90% volume distribution particle size of the artificial graphite negative electrode active material, with a unit of μm;

[0049] R is the disorder degree of the artificial graphite negative electrode active material, which is the ID / IG value obtained by Raman test;

[0050] S is the specific surface area of the artificial graphite negative electrode active material, with a unit of m 2 / g.

[0051] For the artificial graphite negative electrode active material according to the embodiments of the present application, by controlling the relationship among the tap density, electrode plate orientation index, 50% volume distribution particle size, 90% volume distribution particle size, disorder degree and specific surface area of the artificial graphite negative electrode active material, the artificial graphite negative electrode active material has excellent high-temperature cycling performance, and the artificial graphite negative electrode active material is also endowed with good rate performance.

[0052] In some embodiments, 2.0 < HL < 16.0, for example 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, etc., preferably 2.0 < HL < 9.0.

[0053] In some embodiments, the tap density TD is 0.8-1.5 g / cm³. 3 Preferably, it is 1.0-1.3 g / cm³. 3 .

[0054] In some embodiments, the electrode orientation index OI is 4-20, preferably 10-15.

[0055] In some embodiments, the 50% volume distribution particle size Dv50 is 6-20 μm, preferably 10-15 μm.

[0056] In some embodiments, the 90% volume distribution particle size Dv90 is 15-40 μm, preferably 20-25 μm.

[0057] In some embodiments, the disorder degree R is 0.04-0.5, preferably 0.05-0.2.

[0058] In some embodiments, the specific surface area S is 0.6-2.0 m². 2 / g, preferably 0.6-1.5m 2 / g.

[0059] This application also provides a method for preparing an artificial graphite anode active material, comprising the following steps:

[0060] a. After pretreatment, the raw materials are ground, granulated and / or shaped, and then pre-carbonized.

[0061] b. Graphitize the material obtained after pre-carbonization in step a;

[0062] c. Demagnetize the material after graphitization treatment in step b to obtain artificial graphite anode active material.

[0063] In the preparation method of the artificial graphite anode active material in this application embodiment, by controlling the parameters such as the 50% volume distribution particle size Dv50, the 90% volume distribution particle size Dv90, the tap density TD, the electrode orientation index OI, the disorder degree R, and the specific surface area S of the prepared artificial graphite anode active material to meet the requirements of the relationship HL=TD*(OI+Dv50+Dv90) / (100*R*S) and HL>2.0, the high-temperature cycling performance of the artificial graphite anode active material is effectively improved, while taking into account the rate performance of the artificial graphite anode active material.

[0064] In some embodiments, in step a, the raw material includes at least one of needle coke, petroleum coke, pitch coke, and isotropic coke; the pretreatment includes crushing and / or drying; the temperature of the precarbonization treatment is 500-1000℃, and the time of the precarbonization treatment is 1-5h.

[0065] In some embodiments, in step b, the equipment used for graphitization includes at least one of the following: an Atchison crucible furnace, an Atchison box furnace, a horizontal continuous graphitization furnace, a vertical continuous graphitization furnace, a medium-frequency furnace, a medium-frequency continuous furnace, and an electric arc smelting furnace; the temperature of the graphitization is 2000-3000℃, and the time of the graphitization is 1-5h.

[0066] This application also provides a secondary battery, including the artificial graphite anode active material of this application embodiment or the artificial graphite anode active material prepared by the method of this application embodiment. The secondary battery of this application embodiment possesses all the advantages brought by the artificial graphite anode active material of this application embodiment, which will not be repeated here.

[0067] This application also provides an electrical device, including a secondary battery as described in this application embodiment. The electrical device of this application embodiment possesses all the advantages of the secondary battery of this application embodiment, which will not be elaborated further here.

[0068] This application also provides a method for evaluating the high-temperature cycle life of artificial graphite anode active materials, including the following steps:

[0069] (1) The 50% volume distribution particle size Dv50, 90% volume distribution particle size Dv90, tap density TD, electrode orientation index OI, disorder degree R, and specific surface area S of the artificial graphite anode active material were determined. The units for Dv50 and Dv90 are μm, and the unit for TD is g / cm³. 3 The unit of S is m. 2 / g;

[0070] (2) Setting the high-temperature cycling performance index of artificial graphite anode active material

[0071] HL=TD*(OI+Dv50+Dv90) / (100*R*S);

[0072] (3). Based on the Dv50, Dv90, TD, OI, R and S measured in step (1), calculate the high temperature cycle performance index HL of the artificial graphite anode active material. When HL > 2.0, the high temperature cycle life of the artificial graphite anode active material is qualified.

[0073] In the method for evaluating the high-temperature cycle life of artificial graphite negative electrode active materials according to the embodiments of the present application, by studying the influence of core parameters including 50% volume distribution particle size Dv50, 90% volume distribution particle size Dv90, tap density TD, pole piece orientation index OI, disorder degree R and specific surface area S of the artificial graphite negative electrode active material on the high-temperature cycle performance of the graphite negative electrode active material, the relationship between these core parameters and the high-temperature cycle performance of the artificial graphite negative electrode active material is obtained, and a high-temperature cycle performance index HL of the artificial graphite negative electrode active material is proposed as HL=TD*(OI+Dv50+Dv90) / (100*R*S). By judging the value of HL, the high-temperature cycle life of the artificial graphite negative electrode active material can be effectively evaluated; the evaluation method according to the embodiments of the present application can quickly predict the quality of the high-temperature cycle performance of the artificial graphite negative electrode active material before assembling into a test battery. The evaluation method is simple in operation and accurate in judgment result, and it is not necessary to assemble a test battery to test the high-temperature cycle performance, which is conducive to saving time, improving efficiency, and facilitating the rapid advancement of model selection in battery research and development and production.

[0074] In some embodiments, 2.0 < HL < 16.0, preferably 2.0 < HL < 9.0.

[0075] The technical solutions in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by a person skilled in the art without creative efforts shall fall within the protection scope of the present application.

[0076] The raw material sources used in the following examples and comparative examples are as follows:

[0077] Modified petroleum coke: Haike Petrochemical;

[0078] Petroleum coke: Anqing Petrochemical, Daqing Petrochemical;

[0079] Pitch coke: Baowu Carbon;

[0080] Needle coke: Shandong Yida, Jinzhou Petrochemical, Phillips 66.

[0081] Example 1

[0082] Jinzhou needle coke is milled into powder by a mechanical mill, the particle size Dv50 after milling is 10.5 μm, the milled powder is shaped by a shaping machine, and the Dv50 after shaping is 11.8 μm, so as to obtain a shaped material.

[0083] The shaped material is pre-carbonized by high-temperature calcination in a tunnel kiln. The high-temperature calcination process is as follows: the temperature is raised to 500℃ at a heating rate of 3℃ / min and held for 1.5h for the first calcination treatment. Then, the temperature is raised to 1000℃ at a heating rate of 5℃ / min and held for 2h for the second calcination treatment. Finally, the material is discharged at room temperature (25℃) to obtain the pre-carbonized material.

[0084] The pre-carbonized material was graphitized in a medium-frequency continuous furnace at a temperature of 3000℃ for 3 hours to obtain the graphitized material.

[0085] The graphitized material is mixed evenly and then sieved to remove magnetism, thus obtaining artificial graphite anode active material.

[0086] Example 2

[0087] Yida needle coke was ground into powder using a mechanical mill, with a particle size Dv50 of 10.6 μm. After grinding, it was shaped using a shaping machine, with a shaped particle size Dv50 of 11.8 μm, to obtain the shaped material.

[0088] The shaped material is pre-carbonized by high-temperature calcination in a tunnel kiln. The high-temperature calcination process is as follows: the temperature is raised to 500℃ at a heating rate of 3℃ / min and held for 1.5h for the first calcination treatment. Then, the temperature is raised to 1000℃ at a heating rate of 5℃ / min and held for 2h for the second calcination treatment. Finally, the material is discharged at room temperature (25℃) to obtain the pre-carbonized material.

[0089] The pre-carbonized material was graphitized in a medium-frequency continuous furnace at a temperature of 3000℃ for 3 hours to obtain the graphitized material.

[0090] The graphitized material is mixed evenly and then sieved to remove magnetism, thus obtaining artificial graphite anode active material.

[0091] Example 3

[0092] Anqing petroleum coke was ground into powder using a mechanical mill, with a particle size Dv50 of 10.7 μm. After grinding, it was shaped using a shaping machine, with a shaped particle size Dv50 of 11.4 μm, to obtain the shaped material.

[0093] The shaped material is pre-carbonized by high-temperature calcination in a tunnel kiln. The high-temperature calcination process is as follows: the temperature is raised to 500℃ at a heating rate of 3℃ / min and held for 1.5h for the first calcination treatment. Then, the temperature is raised to 1000℃ at a heating rate of 5℃ / min and held for 2h for the second calcination treatment. Finally, the material is discharged at room temperature (25℃) to obtain the pre-carbonized material.

[0094] The pre-carbonized material was graphitized in a medium-frequency continuous furnace at a temperature of 3000℃ for 3 hours to obtain the graphitized material.

[0095] The graphitized material is mixed evenly and then sieved to remove magnetism, thus obtaining artificial graphite anode active material.

[0096] Example 4

[0097] Modified petroleum coke was ground into powder using a mechanical mill to achieve a particle size Dv50 of 10.7 μm. After grinding, the powder was shaped using a shaping machine to achieve a particle size Dv50 of 11.6 μm, resulting in the shaped material.

[0098] The shaped material is pre-carbonized by high-temperature calcination in a tunnel kiln. The high-temperature calcination process is as follows: the temperature is raised to 500℃ at a heating rate of 3℃ / min and held for 1.5h for the first calcination treatment. Then, the temperature is raised to 1000℃ at a heating rate of 5℃ / min and held for 2h for the second calcination treatment. Finally, the material is discharged at room temperature (25℃) to obtain the pre-carbonized material.

[0099] The pre-carbonized material was graphitized in a medium-frequency continuous furnace at a temperature of 3000℃ for 3 hours to obtain the graphitized material.

[0100] The graphitized material is mixed evenly and then sieved to remove magnetism, thus obtaining artificial graphite anode active material.

[0101] Example 5

[0102] Philips 66 needle coke was ground into powder using a mechanical mill to achieve a particle size Dv50 of 15.2 μm. After grinding, the powder was shaped using a shaping machine to achieve a particle size Dv50 of 16.5 μm, resulting in the shaped material.

[0103] The shaped material is pre-carbonized by high-temperature calcination in a tunnel kiln. The high-temperature calcination process is as follows: the temperature is raised to 500℃ at a heating rate of 3℃ / min and held for 1.5h for the first calcination treatment. Then, the temperature is raised to 1000℃ at a heating rate of 5℃ / min and held for 2h for the second calcination treatment. Finally, the material is discharged at room temperature (25℃) to obtain the pre-carbonized material.

[0104] The pre-carbonized material was graphitized in a medium-frequency continuous furnace at a temperature of 3000℃ for 3 hours to obtain the graphitized material.

[0105] The graphitized material is mixed evenly and then sieved to remove magnetism, thus obtaining artificial graphite anode active material.

[0106] Example 6

[0107] Yida needle coke was ground into powder using a mechanical mill to a particle size Dv50 of 8.1 μm. After grinding, the powder was granulated and shaped into a particle size Dv50 of 15.8 μm using a shaping machine to obtain the shaped material.

[0108] The shaped material is pre-carbonized by high-temperature calcination in a tunnel kiln. The high-temperature calcination process is as follows: the temperature is raised to 500℃ at a heating rate of 3℃ / min and held for 1.5h for the first calcination treatment. Then, the temperature is raised to 1000℃ at a heating rate of 5℃ / min and held for 2h for the second calcination treatment. Finally, the material is discharged at room temperature (25℃) to obtain the pre-carbonized material.

[0109] The pre-carbonized material was graphitized in a medium-frequency continuous furnace at a temperature of 3000℃ for 3 hours to obtain the graphitized material.

[0110] The graphitized material is mixed evenly and then sieved to remove magnetism, thus obtaining artificial graphite anode active material.

[0111] Example 7

[0112] Daqing petroleum coke was ground into powder using a mechanical mill to a particle size Dv50 of 10.1 μm. After grinding, the powder was granulated to a particle size Dv50 of 17.8 μm to obtain the granulated material.

[0113] The granulated material was pre-carbonized by high-temperature calcination in a tunnel kiln. The high-temperature calcination process was as follows: the temperature was increased to 500℃ at a heating rate of 3℃ / min and held for 1.5h for the first calcination treatment. Then, the temperature was increased to 1000℃ at a heating rate of 5℃ / min and held for 2h for the second calcination treatment. Finally, the material was discharged at room temperature (25℃) to obtain the pre-carbonized material.

[0114] The pre-carbonized material was graphitized in a medium-frequency continuous furnace at a temperature of 3000℃ for 3 hours to obtain the graphitized material.

[0115] The graphitized material is mixed evenly and then sieved to remove magnetism, thus obtaining artificial graphite anode active material.

[0116] Comparative Example 1

[0117] Philips 66 needle coke was mechanically ground to a particle size Dv50 of 7.1 μm. After grinding, it was granulated to a Dv50 of 15.8 μm to obtain the granulated material.

[0118] The granulated material was pre-carbonized by high-temperature calcination in a tunnel kiln. The high-temperature calcination process was as follows: the temperature was increased to 500℃ at a heating rate of 3℃ / min and held for 1.5h for the first calcination treatment. Then, the temperature was increased to 1000℃ at a heating rate of 5℃ / min and held for 2h for the second calcination treatment. Finally, the material was discharged at room temperature (25℃) to obtain the pre-carbonized material.

[0119] The pre-carbonized material was graphitized in a medium-frequency continuous furnace at a temperature of 3000℃ for 3 hours to obtain the graphitized material.

[0120] The graphitized material was uniformly mixed with 3% asphalt, and then carbonized at 1250℃ for 2 hours in a nitrogen atmosphere. The resulting sample was then mixed evenly and sieved for demagnetization to obtain artificial graphite anode active material.

[0121] Comparative Example 2

[0122] Philips 66 needle coke was mechanically ground to a particle size Dv50 of 7.1 μm. After grinding, it was granulated to a Dv50 of 15.8 μm to obtain the granulated material.

[0123] The granulated material was pre-carbonized by high-temperature calcination in a tunnel kiln. The high-temperature calcination process was as follows: the temperature was increased to 500℃ at a heating rate of 3℃ / min and held for 1.5h for the first calcination treatment. Then, the temperature was increased to 1000℃ at a heating rate of 5℃ / min and held for 2h for the second calcination treatment. Finally, the material was discharged at room temperature (25℃) to obtain the pre-carbonized material.

[0124] The pre-carbonized material was graphitized in a medium-frequency continuous furnace at a temperature of 3000℃ for 3 hours to obtain the graphitized material.

[0125] The graphitized material was uniformly mixed with 5% asphalt, and then carbonized at 1250℃ for 2 hours in a nitrogen atmosphere. The resulting sample was then mixed evenly and sieved for demagnetization to obtain artificial graphite anode active material.

[0126] Comparative Example 3

[0127] Philips 66 needle coke was ground into powder using a mechanical mill to a particle size Dv50 of 6.2 μm. After grinding, it was shaped using a shaping machine to a particle size Dv50 of 7.5 μm, resulting in shaped material.

[0128] The granulated material was pre-carbonized by high-temperature calcination in a tunnel kiln. The high-temperature calcination process was as follows: the temperature was increased to 500℃ at a heating rate of 3℃ / min and held for 1.5h for the first calcination treatment. Then, the temperature was increased to 1000℃ at a heating rate of 5℃ / min and held for 2h for the second calcination treatment. Finally, the material was discharged at room temperature (25℃) to obtain the pre-carbonized material.

[0129] The pre-carbonized material was graphitized in a medium-frequency continuous furnace at a temperature of 3000℃ for 3 hours to obtain the graphitized material.

[0130] The graphitized material was uniformly mixed with 5% asphalt, and then carbonized at 1250℃ for 2 hours in a nitrogen atmosphere. The resulting sample was then mixed evenly and sieved for demagnetization to obtain artificial graphite anode active material.

[0131] Comparative Example 4

[0132] Philips 66 needle coke was mechanically ground to a particle size Dv50 of 7.1 μm. After grinding, it was granulated to a Dv50 of 14.5 μm to obtain the granulated material.

[0133] The granulated material was pre-carbonized by high-temperature calcination in a tunnel kiln. The high-temperature calcination process was as follows: the temperature was increased to 500℃ at a heating rate of 3℃ / min and held for 1.5h for the first calcination treatment. Then, the temperature was increased to 1000℃ at a heating rate of 5℃ / min and held for 2h for the second calcination treatment. Finally, the material was discharged at room temperature (25℃) to obtain the pre-carbonized material.

[0134] The pre-carbonized material was graphitized in a medium-frequency continuous furnace at a temperature of 3000℃ for 3 hours to obtain the graphitized material.

[0135] The graphitized material was uniformly mixed with 5% asphalt, and then carbonized at 1250℃ for 2 hours in a nitrogen atmosphere. The resulting sample was then mixed evenly and sieved for demagnetization to obtain artificial graphite anode active material.

[0136] Comparative Example 5

[0137] Philips 66 needle coke was ground into powder using a mechanical mill to achieve a particle size Dv50 of 9.5 μm. After grinding, the powder was shaped using a shaping machine to achieve a particle size Dv50 of 10.5 μm, resulting in the shaped material.

[0138] The shaped material is pre-carbonized by high-temperature calcination in a tunnel kiln. The high-temperature calcination process is as follows: the temperature is raised to 500℃ at a heating rate of 3℃ / min and held for 1.5h for the first calcination treatment. Then, the temperature is raised to 1000℃ at a heating rate of 5℃ / min and held for 2h for the second calcination treatment. Finally, the material is discharged at room temperature (25℃) to obtain the pre-carbonized material.

[0139] The pre-carbonized material was graphitized in a medium-frequency continuous furnace at a temperature of 3000℃ for 3 hours to obtain the graphitized material.

[0140] The graphitized material was uniformly mixed with 5% asphalt, and then carbonized at 1250℃ for 2 hours in a nitrogen atmosphere. The resulting sample was then mixed evenly and sieved for demagnetization to obtain artificial graphite anode active material.

[0141] Comparative Example 6

[0142] Philips 66 needle coke was mechanically ground to a particle size Dv50 of 7.1 μm. After grinding, it was granulated to a Dv50 of 15.8 μm to obtain the granulated material.

[0143] The granulated material was pre-carbonized by high-temperature calcination in a tunnel kiln. The high-temperature calcination process was as follows: the temperature was increased to 500℃ at a heating rate of 3℃ / min and held for 1.5h for the first calcination treatment. Then, the temperature was increased to 1000℃ at a heating rate of 5℃ / min and held for 2h for the second calcination treatment. Finally, the material was discharged at room temperature (25℃) to obtain the pre-carbonized material.

[0144] The pre-carbonized material was graphitized in a medium-frequency continuous furnace at a temperature of 3000℃ for 3 hours to obtain the graphitized material.

[0145] The graphitized material was uniformly mixed with 3% asphalt, and then carbonized at 1250°C for 2 hours in a nitrogen atmosphere. The carbonized sample was then mixed with the artificial graphite anode active material obtained in Example 5 at a mass ratio of 5:5. After uniform mixing, the mixture was sieved and demagnetized to obtain the artificial graphite anode active material.

[0146] I. The physicochemical parameters of the artificial graphite anode active materials prepared in each embodiment and comparative example were tested, and the test results are shown in Table 1.

[0147] 1. The R-value test method is as follows:

[0148] Take the material powder and test it using a Renishaw Raman spectrometer (inVia Qontor). Perform a Raman spectroscopy on the negative electrode active material with 400 points selected in a 100μm*100μm area and a step size of 5μm. Take the average value of ID / IG (peak intensity ratio).

[0149] 2. Perform particle size distribution (PSD), specific surface area and tap density tests according to the test methods described in GB-T 24533-2019 Graphite Anode Materials for Lithium-ion Batteries.

[0150] 2.1 The particle size testing method is as follows:

[0151] Take the material powder and use a Malvern Mastersizer 3000 laser particle size analyzer with a wet sampler to test and obtain particle size distribution data, taking Dv50 and Dv90.

[0152] 2.2 The specific surface area (BET) test method is as follows:

[0153] The material powder was taken and the specific surface area was measured using a Bestech 3H-2000A dynamic specific surface area tester. The sample was pretreated by vacuum degassing at 200℃ for 2 hours, and then the specific surface area data was obtained.

[0154] 2.3 The method for testing the tap density of powder is as follows:

[0155] Take the material powder and use the Dandong Baite BT-311 tap density meter to test it and obtain the powder tap density.

[0156] 3. The method for testing the electrode orientation index (OI) value is as follows:

[0157] Artificial graphite (anode active material), Super-P (conductive agent), CMC (thickener), and styrene-butadiene rubber (SBR) (binder) were dissolved in deionized water at a weight ratio of 96:1:1.2:1.8 and mixed evenly to prepare a negative electrode slurry. The negative electrode slurry was then uniformly coated onto a copper foil current collector, dried, and cold-pressed. The cold-pressed negative electrode sheet was then analyzed using an X-ray powder diffractometer (X'pert PRO) to obtain the X-ray diffraction pattern, yielding the equation OI = I004 / I110, where I004 is the peak intensity of the 004 characteristic diffraction peak, and I110 is the peak intensity of the 110 characteristic diffraction peak.

[0158] Table 1

[0159]

[0160] Note: HL in the table represents the high-temperature cycling performance index of the artificial graphite anode active material. HL = TD * (OI + Dv50 + Dv90) / (100 * R * S)

[0161] Based on the physicochemical parameters of the artificial graphite anode active materials prepared by the various embodiments and comparative examples in Table 1, the HL values ​​of each embodiment were calculated to be greater than 2.

[0162] II. Electrochemical performance tests were conducted on the artificial graphite anode active materials prepared in each embodiment and comparative example. The test results are shown in Table 2.

[0163] 1. Preparation of lithium-ion batteries:

[0164] The positive electrode active material HLFP (lithium iron phosphate), conductive agent Super-P, and binder polyvinylidene fluoride (PVDF) are dissolved in the solvent N-methylpyrrolidone (NMP) at a weight ratio of 96:2:2 and mixed evenly to form a positive electrode slurry. The positive electrode slurry is then evenly coated onto the current collector aluminum foil, dried, and subjected to cold pressing, edge trimming, cutting, and slitting to form the positive electrode sheet of the lithium-ion battery.

[0165] Artificial graphite anode active material, conductive agent Super-P, thickener CMC, and binder styrene-butadiene rubber (SBR) are dissolved in deionized water at a weight ratio of 96:1:1.2:1.8 and mixed evenly to form a negative electrode slurry. The negative electrode slurry is then evenly coated onto a current collector copper foil, dried, and subjected to cold pressing, edge trimming, cutting, and slitting to form the negative electrode sheet for lithium-ion batteries.

[0166] In an argon-filled glove box, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1 to serve as a non-aqueous organic solvent. Thoroughly dried lithium hexafluorophosphate (LiPF6) at a concentration of 1.2 mol / L was added to the non-aqueous organic solvent, and the mixture was thoroughly mixed to prepare the electrolyte.

[0167] A 12μm polyethylene film (PP) was used as the separator.

[0168] The positive electrode, separator, and negative electrode are wound in sequence, with the separator positioned between the positive and negative electrodes. The length and width of the negative electrode are both greater than those of the positive electrode, resulting in a bare cell. The bare cell is placed in an outer packaging, and the electrolyte prepared above is injected into the dried cell. After standing, formation, and shaping processes, a lithium-ion secondary battery is obtained.

[0169] 2. Initial coulombic efficiency and initial reversible lithium intercalation capacity: Tested according to GB-T 24533-2019 Test Methods for Graphite Anode Materials for Lithium-ion Batteries.

[0170] 3. 45℃ Cyclic Capacity Retention Rate: The battery is charged to 3.65V at 1C constant current and constant voltage in a 45℃ test chamber, and then discharged to 2.5V at 1C for charge and discharge testing.

[0171] 4. Battery rate performance: At 25°C, the prepared battery is fully charged at x C and fully discharged at 1 C. After repeating 10 times, the battery is fully charged at x C, then the negative electrode plate is disassembled, and the lithium precipitation on the surface of the negative electrode plate is observed. If no lithium precipitation occurs on the negative electrode surface, increase the charging rate x C in a gradient of 0.1 C and perform the test again until lithium precipitation occurs on the negative electrode surface, then stop the test. The charging rate (x-0.1) C at this time is the maximum charging rate of the battery.

[0172] Table 2

[0173]

[0174] It can be seen from Table 2 that the batteries prepared from the artificial graphite negative electrode active materials of Examples 1 to 7 of the present application not only have high capacity and initial efficiency, but also have excellent high-temperature cycling performance and rate performance.

[0175] The high-temperature cycling performance index HL of the artificial graphite negative electrode active materials prepared in Examples 1 to 7 of the present application is all greater than 2. The capacity retention rate of the prepared lithium-ion batteries after 100 cycles at 45°C can reach more than 96%, the capacity retention rate after 500 cycles can reach more than 95%, and the capacity retention rate after 1000 cycles can reach more than 93%. Meanwhile, the maximum charging rate of Examples 2, 3, 4, 6 and 7 can be maintained above 1.2 C.

[0176] The high-temperature cycling performance index HL of the artificial graphite negative electrode active materials prepared in Comparative Examples 1 to 6 is all less than 2. Although the lithium-ion batteries prepared from the negative electrode active materials of Comparative Examples 1 to 6 have relatively excellent rate performance, the high-temperature performance at 45°C is significantly reduced. The capacity retention rate after 500 cycles is all lower than 89%, and the capacity retention rate after 1000 cycles even drops below 85%.

[0177] It can be seen that in the present application, by measuring the 50% volume distribution particle size Dv50, 90% volume distribution particle size Dv90, tap density TD, electrode plate orientation index OI, disorder degree R and specific surface area S of the artificial graphite negative electrode active material, and calculating the HL value according to the set formula for the high-temperature cycling performance index of the artificial graphite negative electrode active material: HL=TD*(OI+Dv50+Dv90) / (100*R*S), when HL is greater than 2, it can be determined that the artificial graphite negative electrode active material has excellent high-temperature cycling life. In particular, when 2.0 < HL ≤ 8.4, the artificial graphite negative electrode active material also has good rate performance simultaneously.

[0178] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and should not be construed as limiting the present application. A person skilled in the art may make changes, modifications, substitutions and variations to the above embodiments within the scope of the present application.

Claims

1. A synthetic graphite anode active material, characterized in that, The artificial graphite negative electrode active material satisfies: HL=TD*(OI+Dv50+Dv90) / (100*R*S), HL>2.0; Wherein, TD is the tap density of the artificial graphite negative electrode active material, in g / cm³. 3 ; OI is the pole piece orientation index of an electrode plate prepared from the artificial graphite negative electrode active material; Dv50 is the 50% volume distribution particle size of the artificial graphite negative electrode active material, with the unit of μm; Dv90 is the 90% volume distribution particle size of the artificial graphite negative electrode active material, with the unit of μm; R is the disorder degree of the artificial graphite negative electrode active material, which is the ID / IG value obtained by Raman test; S represents the specific surface area of ​​the artificial graphite anode active material, in m². 2 / g.

2. The artificial graphite anode active material according to claim 1, characterized in that, 2.0<HL<16.0, preferably 2.0<HL<9.

0.

3. The artificial graphite anode active material according to claim 1, characterized in that, The tap density TD is 0.8-1.5 g / cm³. 3 Preferably, it is 1.0-1.3 g / cm³. 3 . and / or, the pole piece orientation index OI is 4-20, preferably 10-15; and / or, the 50% volume distribution particle size Dv50 is 6-20 μm, preferably 10-15 μm; and / or, the 90% volume distribution particle size Dv90 is 15-40 μm, preferably 20-25 μm; and / or, the disorder degree R is 0.04-0.5, preferably 0.05-0.2; And / or, the specific surface area S is 0.6-2.0 m². 2 / g, preferably 0.6-1.5m 2 / g.

4. A method for preparing an artificial graphite anode active material according to any one of claims 1-3, characterized in that, comprises the following steps: a. subjecting raw materials to pretreatment, then performing powder milling, granulation and / or shaping, followed by pre-carbonization treatment; b. graphitizing the material obtained after pre-carbonization in step a; c. demagnetizing the graphitized material obtained in step b to prepare the artificial graphite negative electrode active material.

5. The method for preparing the artificial graphite negative electrode active material according to claim 4, characterized in that, In said step a, the raw materials comprise at least one selected from needle coke, petroleum coke, pitch coke and isotropic coke; the pretreatment comprises crushing and / or drying; the temperature of the pre-carbonization treatment is 500-1000°C, and the duration of the pre-carbonization treatment is 1-5 h.

6. The method for preparing the artificial graphite negative electrode active material according to claim 4 or 5, characterized in that, The temperature of the graphitization treatment is 2000-3000°C, and the duration of the graphitization treatment is 1-5 h.

7. A secondary battery, characterized in that, comprises the artificial graphite negative electrode active material according to any one of claims 1-3 or the artificial graphite negative electrode active material prepared by the method according to any one of claims 4-6.

8. An electrical device, characterized in that, comprises the secondary battery according to claim 7.

9. A method for evaluating the high-temperature cycle life of an artificial graphite anode active material, characterized in that, comprises the following steps: (1) The 50% volume distribution particle size Dv50, 90% volume distribution particle size Dv90, tap density TD, electrode orientation index OI, disorder degree R, and specific surface area S of the artificial graphite anode active material were determined. The units for Dv50 and Dv90 are μm, and the unit for TD is g / cm³. 3 The unit of S is m. 2 / g; (2). setting a high-temperature cycle performance index of the artificial graphite negative electrode active material HL=TD*(OI+Dv50+Dv90) / (100*R*S); (3). calculating the high-temperature cycle performance index HL of the artificial graphite negative electrode active material according to Dv50, Dv90, TD, OI, R and S measured in step (1), and when HL>2.0, the high-temperature cycle life of the artificial graphite negative electrode active material is evaluated as qualified.

10. The method for evaluating the high-temperature cycle life of the artificial graphite anode active material according to claim 9, characterized in that, 2.0<HL<16.0, preferably 2.0<HL<9.0.